2004
DOI: 10.1007/s11104-005-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fertilization and water stress affects plant water relations, stomatal conductance and osmotic adjustment in chickpea (Cicer arientinum L.)

Abstract: Chickpea (Cicer arietinum) is an important dryland pulse crop in many parts of the world. Productivity is often limited by periods of water deficit and in a number of regions zinc deficiency occurs, but the interaction between zinc nutrition and water stress has not been studied extensively. This interaction was examined in two glasshouse experiments. Chickpea was grown under deficient (no applied Zn) or adequate (2.5 µg Zn/g soil) levels of zinc in pots for either 53 days (Experiment 1) or 40 days (Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 29 publications
8
63
0
Order By: Relevance
“…Zn deficiency decreases yield and delays crop maturity. It also reduces water use and water use efficiency (Khan et al, 2004), as also root nodulation and hence nitrogen fixation (Shukla and Yadav, 1982). Zn deficiency can be easily overcome by soil application and by foliar application of Zn fertilizers (Roy et al, 2006).…”
Section: Resumen Comunicación Corta Respuesta Del Garbanzo a Las Aplmentioning
confidence: 99%
“…Zn deficiency decreases yield and delays crop maturity. It also reduces water use and water use efficiency (Khan et al, 2004), as also root nodulation and hence nitrogen fixation (Shukla and Yadav, 1982). Zn deficiency can be easily overcome by soil application and by foliar application of Zn fertilizers (Roy et al, 2006).…”
Section: Resumen Comunicación Corta Respuesta Del Garbanzo a Las Aplmentioning
confidence: 99%
“…Zn deficiency decreases crop yield and delays crop maturity. Also, Zn deficiency reduces water use and water use eff iciency (Khan et al, 2004) and also reduces nodulation and nitrogen fixation (Ahlawat et al, 2007), which contributes to a decrease in crop yield. In neutral to alkaline soils, Zn deficiencies can be encountered (Roy et al, 2006), Zn solubility decreases markedly above pH 6.0-6.5 (Sims, 2000).…”
mentioning
confidence: 99%
“…The independent effects of Mn, B and Zn may have a role in alleviating the damaging effects of drought on crop plants. Boron, Zinc and Mn applications raise the resistance of plants to drought stress (Azza et al, 2006, Khan et al, 2004, Movahhedy-Dehnavy et al, 2009and Wei et al, 2005.Field observation of barley has indicated that adequate Zn nutrition can increase drought tolerance (King 1994), while decrease in grain yield due to drought stress in wheat was shown to be more marked when plants were Zn deficient (Bagci et al, 2007 andEkiz et al, 1998).It has been established that micronutrients could prevent the suppression of leaf elongation under drought and finally the shoot dry matter production (Fukai et al, 1999, Pant et al, 1998and Peleg et al, 2008.…”
Section: Effect and Drought Stress Management Strategies In Wheat Cropmentioning
confidence: 99%